2008
DOI: 10.1016/j.jfms.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the subcutis of the nose in a cat caused by Mucor species: Successful treatment using posaconazole

Abstract: A 14-year-old neutered female domestic shorthair cat was presented for investigation of a non-painful subcutaneous swelling of the nasal dorsum at the site of a scratch injury. Cytological evaluation demonstrated a granulomatous reaction and many variably shaped organisms consistent with yeasts/fungi. Subsequent biopsy and culture yielded a pure growth of a Mucor species. The cat was treated with the second-generation triazole antifungal agent posaconazole for 5 months. Complete resolution was seen with no rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…17 Although there is a single case report of a cat with subcutaneous nasal Mucor species infection that responded to oral posaconazole alone, there are no such reports in cats with Cladophialophora species infection. 31 A cat with a pulmonary granuloma containing Cladophialophora species was treated with posaconazole for 7 months after surgical removal of the granuloma but relapsed within 4 weeks after the drug was discontinued. 7 Malachite green is a triphenylmethane chemical dye used in the fish and dye industries that possesses antifungal, antiparasitic and antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although there is a single case report of a cat with subcutaneous nasal Mucor species infection that responded to oral posaconazole alone, there are no such reports in cats with Cladophialophora species infection. 31 A cat with a pulmonary granuloma containing Cladophialophora species was treated with posaconazole for 7 months after surgical removal of the granuloma but relapsed within 4 weeks after the drug was discontinued. 7 Malachite green is a triphenylmethane chemical dye used in the fish and dye industries that possesses antifungal, antiparasitic and antibacterial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Successful treatment with posaconazole has been reported in 2 cats with fungal disease in which other antifungal treatment had failed . Those cases involved a Mucor subcutis infection of the nose and invasive orbital aspergillosis.…”
Section: Discussionmentioning
confidence: 99%
“…Successful treatment with posaconazole has been reported in 2 cats with fungal disease in which other antifungal treatment had failed. 12,13 Those cases involved a Mucor subcutis infection of the nose and invasive orbital aspergillosis. For the cat with aspergillosis, antifungal susceptibility testing for the organism was completed and showed that posaconazole was the most effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…), and in a cat with infection of the subcutis of the nose caused by Mucor species (Wray et al . ). Hepatotoxicity can occur, but rarely results in hepatic failure (Courtney et al .…”
Section: Introductionmentioning
confidence: 97%